A Demonstration of Equivalence between Parameter-Induced and Noise-Induced Stochastic Resonances with Multiplicative and Additive Noises - 李建龙 曾令藻 章惠全 (Chinese physics letters, 2010)
A typical bistable nonlinear system with multiplicative and additive noises can produce stochastic resonance （SR） by increasing the intensity of the additive noise or the multiplicative noise and it has been proved that SR can also be realized by tuning system parameters. We clearly demonstrate the equivalence between parameter-induced SR （PSR） and noise-induced SR in the presence of multiplicative and additive noises. By tuning several system parameters with fixed noise intensities, the SR is induced just as it is realized by tuning the additive noise or the multiplicative noise. It may be interesting to realize PSR when the noise intensity exceeds the resonance level, or when the characteristic of the noise is unknown.